Sex and Ontogenetic Variation in the Crest of Numida meleagris: Implications for Crested Vertebrates. Issue 4 (8th November 2019) - Angst, Delphine; Barnoud, Jonathan; Cornette, Raphaël; Chinsamy, Anusuya
ABSTRACT: Crested vertebrates are known from a wide variety of modern and fossil taxa, however, the actual formation and function of the crest is still debatable. Among modern birds, the globally distributed guinea fowl ( Numida meleagris ) is characterized by having a cranial bony crest (overlain by keratin), but surprisingly little is known about its development. Here, we studied the crest of 202 wild guinea fowl from the same population, using anatomical measurements as well as 2D‐morphometry. Our results show that juveniles have smaller skulls than adults and have smaller, simpler crests that are visible even in very young individuals. Among adults, female skulls are smaller than males, and they have smaller, simpler shaped crests, which permit a discrimination between the sexes of 93% when the keratin is preserved with the bony crest, and of 89% when only the bony crest is available. By extrapolation, these results confirm that the crest can be used as an ontogenetic character, as well as for sex discrimination in the fossil record. Our results also show that the overlying keratin does not always mimic the underlying bony crest, which should be considered when reconstructing extinct crested vertebrates. Anat Rec, 303:1018–1034, 2020. © 2019 American Association for Anatomy